The Determination of Education, Work Achievement, and Work Experience on Career Development - Hafisya Agnesia; Rika Lidyah (Takaza Innovatix Labs Ltd., 2026)
Employee career development is an important aspect in improving organizational performance and sustainability, especially in public transportation companies such as PT Kereta Api Indonesia (Persero). This study aims to analyze the influence of education, work performance, and work experience on the career development of employees at PT Kereta Api Indonesia (Persero) Lubuk Linggau Station. The research method used is a quantitative approach with a field research design. Data were collected through a closed questionnaire using a five-point Likert scale distributed to 50 employees as respondents, with instruments that had been tested for validity and reliability. Data analysis was performed using multiple linear regression, classical assumption tests, t-tests, and F-tests. The results showed that education, work performance, and work experience had a positive and significant effect on employee career development, both partially and simultaneously, with work performance being the most dominant variable. In conclusion, improving the quality of education, optimal performance, and adequate work experience plays an important role in supporting employee career development, which can serve as a basis for organizations in formulating more effective and sustainable career development policies.